PENERAPAN AKUNTANSI, AKUNTABILITAS DAN PENGENDALIAN INTERNAL PADA GEREJA KRISTEN EQUITY JAWA WEDI - Prabowo, Wahyu Jati Agung; Kurniasih, Lulus (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This study discusses the application of accounting, accountability andinternal control contained in the Gereja Kristen JawaWedi Klaten, because a lot of corruption in religious institutions. The purpose of this study was to analyze and evaluate the implementation of accounting, accountability and internal controls exist in Gereja Kristen Jawa Wedi Klaten. The method used in this research is qualitative descriptive method, that is by direct observation, interviews, and literature. This research was conducted in Gereja Kristen JawaWediKlaten which is a non-profit religious organization. Research results obtained Gereja Kristen Jawa Wedi Klaten namely the application of accounting, accountability, and internal controls are already well underway, but there are some shortcomings that reporting is not in accordance with IAS 45, the employee who is not competent, and yet there is a good division of labor